Programa de proteção a vítimas e testemunhas ameaçadas - Provita: um estudo sobre o serviço social - Santa, Elaine Christina (2006)
The purpose of this research analyses The Victims and Threatened Witnesses Program of Protection - Provita - appears, in 1996, from an initiative of the civil society in partnership with the State. As a result of this process, in July 13 1999, is promulgated the Federal Law nº 9.807, that establishes standards for the organization and maintenance of this Program. The focus of this Program is the reduction of the impunity, creating security conditions to the threatened witnesses. From a revision of the historical construction process of the national security system, it is considered as a basic guarantee instrument to the right to the life and to the security, in a context where the violence and impunity are daily expressed realities. During the research process, we aimed to better understand the inter-relations, connections and factors responsible for the existence of this Program in our Brazilian society and the Social Service role. So, the objective of this research is centered on studying the social worker job in this Program, approaching questions on its attributions, objectives and challenges. It aims to reflect on professional practices, in the prism of human rights defense, in accordance with what was praised in the Code of Professional Ethics. This research concludes the require and importance of enlargement of the responsibility of the State about execution of public security activities, when the limitations were given to the development of the service created, between other factors, by the absence of articulation with the set of public politics, essential policies for the service to the necessities of the persons in regime of protection; resource insufficiency for the formation and security of the professionals group; slowness of the judicial processing. The data, between 2000 and 2005, of 75 people protected, of which 21 testified in processes that reached the final verdict, and 20 turned in condemnatio n, illustrate both the importance and the difficulties of the Program. We also perceived that the social worker practice still is permeated by the challenge of acting and implementing the commitment with its practice citizens. This professional has the dut y of working in search for the citizenship promotion, the emancipation and to make possible the conditions of the protected person of struggle for his rights, during the protection process and over all, later